Current trends strategies in the test redundancy reduction - Norasyikin, Safieny; Kamal Z., Zamli; Hasneeza, L. Zakaria (2016)
Software testing is most important and expensive part in software development process. The failures of software can lead disastrous consequence, such as loss of data, fortune and lives. This process usually expensive, and the key of expensiveness of testing is that typically take a long time to execute the whole set of test cases. Test case minimization technique generates a representative set from the original test suite that satisfy all the requirements as an original test suite but contains less number of test cases. Redundant test cases are removed from the test suite. Many strategies in a greedy approach have been developed (including GE, GRE, and HGS), Formal Concept Analysis and non-greedy approach (tReductLAHC, tReductSA) using Metaheuristic Algorithm. The non-greedy approach is more effective compared to greedy approach. In this paper, a review of the strategies is provided to investigate the current trends in the test reduction research area. We can categorize these strategies as Greedy and Metaheuristic Approach. To enhance the performance by using a metaheuristic algorithm, we are proposing our work with adopts the sequence permutation and hybridization strategies.